2020
DOI: 10.1108/ccij-02-2020-0044
|View full text |Cite
|
Sign up to set email alerts
|

Exploring strategic CSR communication on UAE banks' corporate websites

Abstract: PurposeCommunicating CSR through corporate websites is one of the most effective ways for organizations to inform and engage stakeholders, earn legitimacy and reap the intangible and tangible benefits of practicing CSR. However, in emerging economies in the Middle East, online CSR disclosure remains limited while corporate websites are not used effectively as strategic tools. This study explores online CSR communication (CSRC) by banks in the dynamic, emerging economy of the United Arab Emirates.Design/methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 49 publications
4
31
1
1
Order By: Relevance
“…In another study, Khalil and O'sullivan (2017) analyzed the social and environmental reporting of 34 Lebanese banks and showed that profitability, size, leverage and ownership concentration have an impact on CSR disclosures. Furthermore, Georgiadou and Nickerson (2020) investigated 28 websites of banks from the United Arab Emirates and found that domestic/government-owned and conventional banks communicate CSR initiatives more prominently and extensively than private and Islamic banks do.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Khalil and O'sullivan (2017) analyzed the social and environmental reporting of 34 Lebanese banks and showed that profitability, size, leverage and ownership concentration have an impact on CSR disclosures. Furthermore, Georgiadou and Nickerson (2020) investigated 28 websites of banks from the United Arab Emirates and found that domestic/government-owned and conventional banks communicate CSR initiatives more prominently and extensively than private and Islamic banks do.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the volume of research on CSR disclosures on bank websites has increased, knowledge about them remains insufficient. Owing to the importance of websites as a medium for communicating social responsibility information, online CSR reporting has become a focus area for scholars (Branco and Rodrigues, 2006; Bravo et al , 2012; Chakroun et al , 2017; Georgiadou and Nickerson, 2020; Hetze and Winistörfer, 2016; Hinson, 2011; Hinson et al , 2010; Khalil and O'sullivan, 2017; Matuszak and Rózańska, 2019; Vilar and Simão, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Garde Sanchez et al , 2013; Rodriguez Bolìvar et al , 2013; Garde Sanchez et al , 2021); banks (e.g. Sobhani et al , 2012; Kiliç, 2016; Palazzo et al , 2020; Georgiadou and Nickerson, 2020); the hospitality industry (e.g. Hsieh, 2012; Iazzi et al , 2020) and agro-food (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some geographic nouns in the citation network overlapped across two or more continents such as the “Middle East” which includes countries in North Africa, Asia, Europe, and even the Mediterranean because of its Islamic ethnic and cultural emphasis (Georgiadou & Nickerson, 2020; Jamali et al., 2020; Naguib & Jamali, 2015; Soltani et al., 2015). Similar regions bound by ethnicity and culture include “Latin America” and “Southeast Asia.” These were also referred to without reference to their sub‐contexts either, thus muddying the developmental waters even further.…”
Section: Results: Diagnostic Presentation and Discussionmentioning
confidence: 99%